Application of Water Quality Index as a vulnerability indicator to determine seawater intrusion in unconsolidated sedimentary aquifers in a tropical coastal region of Sri Lanka - Chandrajith, Rohana; Bandara, U. G. Chaminda; Diyabalanage, Saranga; Senaratne, Sachintha; Barth, Johannes (Groundwater for Sustainable Development, 2022)
Coastal freshwater aquifers are under threat and in many cases gradually decline due to climate change and over-extraction of water with the rapidly expanding human activities including agriculture and tourism. In this study, coastal sedimentary aquifer systems in northern Sri Lanka were characterized by integrated approaches such as mass balance calculations, Seawater Mixing Index (SMI) and Water Quality Index (WQI). A total of 34 groundwater samples were collected and analyzed for field parameters (pH, electrical conductivity (EC), dissolved oxygen and temperature) their major ions (Ca2+, Mg2+, Na+, K+, Cl-, SO42−, NO3−, HCO3−) and selected trace elements (Sr, Ba, B) as well as stable water isotopes (δ18OH2O and δ2HH2O). The EC in investigated groundwater samples ranged from 81 to 5690 μS/cm (mean - 1260 μS/cm) and served as the first indication of seawater intrusion. The study region consists of predominantly Ca2+-HCO3− and Na+-Cl- water types indicating freshening and seawater intrusions as revealed by a Hydrogeochemical Facies Evaluation (HFE) diagram. The WQI and SMI approach indicated that in the study region, 50–58% of samples are affected by seawater intrusion. Up to 28% of seawater admixture was noted based on the mass balance calculation using Cl- (0.55–156 meq/L) as a conservative tracer. This result significantly correlates with the calculated WQI (r = +0.944; p < 0.000). Water isotope values indicated that most of the groundwater in the area is recharged directly from precipitation while some samples showed influences of evaporation and also mixing with seawater. In summary, the investigated coastal sedimentary aquifer system in the northern part of Sri Lanka is already severely affected by seawater intrusion. However, as marked by the dissolution of carbonate minerals under the influence of monsoonal rains leads to the freshening of groundwater. This study showed that WQI combined with mass balance calculations is useful in assessing the vulnerability of coastal aquifers in arid and semi-arid regions.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Arid and semi-arid zone aquifers; Hydrogeochemical facies evaluation diagram; Mass balance calculation; Sedimentary aquifers; Water isotopes